Perancangan Karakter Female Sci-Fi Dengan Model Visual 3D Dalam Game Eclipse of The Undead Di PT. Miracle Grup Indonesia: Bahasa Indonesia - Lee, Evelien; Krisna Ari, Ida Ayu Dwita; Segara Putra, Gede Bayu (Program Studi Desain Komunikasi Visual, 2024)
Several years ago, games were associated with playing outside with friends, going on adventures, and doing physical activities that improved children's motor skills. However, today video games are better known than traditional games, with fun applications that can be played on various devices. The world is developing; 2D visuals are still used with more impressive animations and brilliant colours that are pleasing to the eye, but the new visual form, namely 3D, is no less interesting. Various ideas from digital game producers are expressed in visual form in the form of 2D and 3D, but as time goes by 3D visuals are gaining a wider audience. PT. Miracle Group Indonesia, which was founded in 2014, empowers 3D Artists to design various 3D models with realistic, stylized, and cartoon styles. Currently, PT. Miracle Group Indonesia is in the game development stage, Battle of Guardians which has been launched on the Steam platform on PC. Apart from Battle of Guardians, PT. Miracle Group Indonesia is also in the development stage of various new video games; Eclipse of the Undead is one of them. Eclipse of the Undead is a video game with 3D visuals that takes the player as the main character in a post-pandemic world that has filled the world with zombies and monsters. To increase knowledge in character design with 3D visual models and as proof that Indonesian children can also compete and are indeed capable of creating 3D models/assets like other countries, this writing is expected to provide significant new knowledge.